Characterising the morphological characters and carbohydrate metabolism of oat culms and their association with lodging resistance. (12th December 2019) - Zhang, R.; Jia, Z.; Ma, X.; Ma, H.; Zhao, Y.
Abstract: Lodging resistance can be improved by enhancing the mechanical strength of culms, and culm carbohydrates could improve this mechanical strength. Culm carbohydrates can regulate development of the culm and affect its toughness. The present study determines the relationship between lodging and carbohydrate content in oat culms. Field experiments were conducted in alpine regions in 2017 and 2018 using three oat varieties with different lodging resistance. Lodging‐related morphological characteristics were directly determined and culm carbohydrate content and enzyme activity related to cellulose synthesis and sucrose metabolism were evaluated with ultraviolet spectrophotometry. Results showed that the lower the gravity height or the lower ratio of gravity height to plant height, the stronger the lodging resistance of the varieties. Higher culm nonstructural (NSC) and structural (SC) carbohydrate content contributed to the ability of culms to resist lodging, especially the content of cellulose and sucrose. PCA showed that sucrose metabolism and SC content were closely related to lodging resistance. Correlation analysis showed that the lodging index (LI) was significantly negatively correlated with NSC. Sucrose content was highly and significantly positively correlated with NSC. Additionally, the activities of sucrose phosphate synthase (SPS) and sucrose synthase (SS) were highly and significantly positively correlated with sucrose and cellulose content. The relationship between field characters and oat lodging, as well as the regulatory mechanism of carbohydrate content on lodging resistance of the culm are discussed. Abstract : The morphological characteristics and carbohydrate content of 3 oat cultivars with different lodging resistance were determined, and results showed that gravity height and the ratio of gravity height to plant height, the content of cellulose and sucrose were significantly correlated related to lodging resistance.